Pengembangan Model Penciptaan Lagu Rohani - Yohanes, I Nyoman; Suharsono, Naswan; Tegeh, I Made (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2017)
The purpose of this study is to describe the ways the spiritual songwriter creating their songs, weave patterns or how they are to be used as a model of hymns writng that can be implemented by others. Design used is research and development. Research conducted on some of the literature related to the birth stories of spiritual songs. Development is done on the model creation hymns, as the combination of the results of the research literature and research experience in creating spiritual songs. Data collection methods that researchers use is the study of literature. interviews and try quisener the subject. Data were analyzed by descriptive qualitative. Through this study has developed a model of the creation of spiritual songs that can be implemented by others. The model developed includes the steps of: a simple poem procurement, laying of lines bars, beats determination, giving tone and perform melodic refinement by utilizing certain ethnic scales.